Pengaruh Bimbingan Belajar Guru Terhadap Hasil Belajar Peserta Didik Di SDI Tetandara Kecamatan Ende Tengah Kabupaten Ende - Benedikta Boleng (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2022)
Formula in research this is (1) How level teacher's guidance to also educate in SDI Tetandara Kecamatan Ende Tengah Kabupaten Ende? ( 2) does result study also educate SDI Tetandara Kecamatan Ende Tengah Kabupaten Ende? (3) What there is influence that positive and significant of guidance study teacher in result study student SDI Tetandara, Kabupaten Ende. this research Aim is (1) To to know form guidance in also educate in SDI Tetandara Ende Tengah Kabupaten Ende (2) To to know result study also educate in SDI Tetandara Ende Tengah Kabupaten Ende (3) To to know what there is influence positive and significant of guidance study teacher in result study student SDI Tetandara, Kabupaten Ende. This Research to use it the quantitative research method ex's type-post facto . In to gather it examiner data to use it inquiry and result data study student. Sub j ek in this research ad class student alah IV, V, IV SDI Tetandara. the Data that collected be analyzed with to use it analysiical regresi linear simple with assisting of SPSS for program version windows 16. Result To be based data analysiical be obtained result that got the influence that positive and significant of guidance study teacher in result study also educate SDI Tetandara Ende Tengah Kabupaten Ende with value 0,000 < 0.05 or t count 5,898 > table t 1,701 and determinasi's coefficient as big as 0,191 or 19,1.